Cover Crop Effects on Soybean in a Soybean/Corn Rotation - D. E. Shoup; I. A. Ciampitti; J. Kimball; Gretchen Sassenrath (Kansas Agricultural Experiment Station Research Reports, 2017)
A research study was established in 2011 in a soybean and corn rotation with cover crops planted soon after each crop harvest in the fall. A variety of complex cover crop mixtures were evaluated ranging from single specie to 7 specie mixtures. Cover crops were terminated in the spring soon after anthesis of the cool season cereal in the cover crop. Soybean yield responded differently among the four years of the study. In an extreme drought year of 2012, the unplanted check yielded 29.4 bu/a. Soybean yield was significantly reduced by 4.2 and 3.4 bu/a in treatments with wheat or turnip cover crop, respectively. In 2014, the unplanted check yielded 33.9 bu/a and cover crop treatments rye, rye + radish, and>6-species mix had significantly greater soybean yield at 3.7, 3.4, and 3.3 bu/a, respectively. In 2015, only the rye cover crop treatment significantly reduced soybean yield compared to the unplanted check at a 4.2 bu/a yield loss. No significant yield differences were observed in any cover crop treatment in 2016.
Keywords: cover crop; soybean; rye; radish